STAGES OF DEVELOPMENT AND IMPACT ON SOCIAL LIFE OF AN INFORMED SOCIETY IN UZBEKISTAN - Elbek Ganiyev (Western European Studies, 2024)
In this article, the influence of the information society and their manifestation in the formation of the worldview of modern youth is emphasized. In the world, the processes of globalization cause the development of innovative ideas and the acceleration of the information society, radical renewal, change and new development. In such situations, human activity requires a rational attitude to the scientific, social, spiritual, political, economic and ecological processes taking place
Keywords: globalization; information; information society